Perencanaan Kerangka Kerja Menggunakan The Open Group Architecture Framework-Architecture Development Method (TOGAF-ADM) pada Puskesmas Sukatani - Eryan Ahmad Firdaus; Shanti Maulani (Jurnal Sistem Informasi Galuh, 2023)
Problems occurred at the Sukatani Health Center is that they do not have their own information system; they still use applications provided by the Health Office; furthermore, they have not fully utilized technology, only partially in processing reports. In accordance with the existing fact that the utilization of information systems is beneficial in business process activities. Hence, it is necessary to plan or design Information System architecture at the Sukatani Health Center to facilitate activities in carrying out business processes, especially in medical services and medical support in order to be more effective and efficient. Based on the research, information system architecture planning at the Sukatani Public Health Center is divided into two architectures: data architecture and application architecture. The data architecture resulted in a classification of 47 classes’ data from all business processes. The application architecture resulted in the classification of 21 application candidates in 6 information system areas; namely the patient admissions information system area consisted of 4 application candidates, the medical service information system area consisted of 6 application candidates, the medical support information system area consisted of 2 application candidates, the pharmacy installation information system area consisted of 3 application candidates, the nutrition installation information system area consisted of 2 application candidates, and the payment information system area consisted of 4 application candidates.